Francisco Leocata and the history of Christian philosophy in Argentina (Tábano, 2024)
This paper proposes, through an analysis of Francisco Leocata's works on the history of philosophical ideas in Argentina, to distinguish three lines of force or three ways of doing in philosophy in harmony with the Christian faith. Two of these have been present since the beginning of the colonial period and are progressively entering into dispute, while a third is emerging within the framework of what is known as Latin American thought. To achieve this, it will be necessary to first elucidate two presuppositions: what the author understands by Christian philosophy and why it is important to distinguish modernity from the Enlightenment. Following this, there will be a critical historical review of Argentine thinkers, more or less related to Christianity, who will be classified based on their rejection or support for the ideas of modernity/enlightenment. Finally, it is suggested to recognize, as a derivative of these reflections, a third position in the thought of Juan Carlos Scannone.
Keywords: Leocata; Modernity; Enlightenment; Christianity; Scanonne